2023
DOI: 10.1155/2023/1631978
|View full text |Cite
|
Sign up to set email alerts
|

The Components of the Spiritual Intelligence Predicting the Mental Toughness and Emotional Creativity for the University Students

Abstract: The present study aims to investigate the components of spiritual intelligence that predict mental toughness and emotional creativity. It also reveals the statistically significant differences in spiritual intelligence, mental toughness, and emotional creativity in terms of the gender and academic specialization variables. The measurements of spiritual intelligence, mental toughness, and the measurement of emotional creativity have been applied to a sample study consisting of 192 male and female students from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It is about how an individual's work aligns with their spiritual convictions (Chirico, Acquadro & Sharma, 2023;Delle & Segaro, 2023). Spirituality has potential influence in the career planning process, including its significant impact on an individual's values, career choices, job satisfaction, life meaning, and mental/spiritual well-being (Hassan, 2023;Jondar, Sampaleng & Halim, 2023;Yadollahpour, Nouriani, Faramarzi, Yaminfirooz, Shams & Gholinia, 2023;Hsiao, Chien & Li, 2009). The studies on spiritual well-being indicate that the top priority for spiritual health is to know oneself truthfully and accept oneself (Hung, 2008).…”
Section: Spirituality and Spiritual Cultivationmentioning
confidence: 99%
“…It is about how an individual's work aligns with their spiritual convictions (Chirico, Acquadro & Sharma, 2023;Delle & Segaro, 2023). Spirituality has potential influence in the career planning process, including its significant impact on an individual's values, career choices, job satisfaction, life meaning, and mental/spiritual well-being (Hassan, 2023;Jondar, Sampaleng & Halim, 2023;Yadollahpour, Nouriani, Faramarzi, Yaminfirooz, Shams & Gholinia, 2023;Hsiao, Chien & Li, 2009). The studies on spiritual well-being indicate that the top priority for spiritual health is to know oneself truthfully and accept oneself (Hung, 2008).…”
Section: Spirituality and Spiritual Cultivationmentioning
confidence: 99%
“…A study involving students at Trabzon University who participated in team and individual sports revealed that Emotional Intelligence (EI) and Spiritual Intelligence (SI) are factors in increasing creativity (Aydin, 2019). Another study suggested that SI can predict emotional resilience and creativity with insight into challenges and mindfulness serving as significant predictors (Hassan, 2023). The relationship between SI and creativity acts as a mediator between EI and creativity indicating that individuals with high levels of EI are more likely to show bias when they also have strong SI.…”
Section: Introductionmentioning
confidence: 99%